Interpretasi Citra Satelit Landsat 8 Untuk Identifikasi Kerusakan Hutan Mangrove di Taman Hutan Raya Ngurah Rai Bali - I WAYAN RUMADA; A. A. ISTRI KESUMADEWI; R. SUYARTO (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2015)
ABSTRACT A study of Landsat 8 satellite image interpretation for identification of mangrove forest destruction in Forest Park Ngurah Rai Bali A study of Landsat 8 satellite image interpretation for identification of mangrove forest destruction in Forest Park Ngurah Rai Bali, was conducted in March-July 2014. The study was aimed to determine the damage and condition of the mangrove forest in 2013. Remote sensing techniques was applied through analysis and interpretation of NDVI (Normalized Difference Vegetation Index). The landsat 8 image that was used in this study issued by (USGS 2013), and the path and row was (116/66). The NDVI result was confirmed by purposive field survey on selected area. The results of the study showed that the damage on mangrove Forests can be classified into three classes based on NDVI analysis. These classification was as follows (a) severely damaged with an area of ??20,25 hectares, (b) slightly damaged with an area of ??22,86 hectares, and (c) not damaged with an area of ??1.042,02 Ha. According to this finding the accuracy of NDVI analysis for identification mangrove canopy density in this study was 75% for mangrove land use type 90%. Keywords: NDVI (Normalized Difference Vegetation Index), Satellite Imagery, Mangrove Forest Damage Level.